2021
DOI: 10.1108/bij-10-2020-0534
|View full text |Cite
|
Sign up to set email alerts
|

Family incivility, burnout and job satisfaction: examining the mediation effect

Abstract: PurposeDrawing from the work-home resources model and the conservation of resources theory, this study examines the potential of family incivility in instigating burnout and reduced job satisfaction.Design/methodology/approachThis study employed structured questionnaires to collect data from a sample of 290 doctors working in tertiary care hospitals across India. Measurement modeling was done using IBM AMOS 23.0 and PROCESS macro was employed for hypothesis testing.FindingsThe study revealed that family incivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(48 citation statements)
references
References 89 publications
(187 reference statements)
3
43
0
Order By: Relevance
“…Running Model 4, we found a significant mediation effect of family incivility on job satisfaction through burnout (coefficient = 0.25 and 95% confidence intervals (CI) = 0.16, 0.24), based on bias-corrected confidence intervals derived from 5,000 bootstrapped samples (Preacher and Hayes, 2004). Thus, the result that burnout mediated the pathway between family incivility and job satisfaction is consistent with previous research findings (Paul et al. , 2021).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Running Model 4, we found a significant mediation effect of family incivility on job satisfaction through burnout (coefficient = 0.25 and 95% confidence intervals (CI) = 0.16, 0.24), based on bias-corrected confidence intervals derived from 5,000 bootstrapped samples (Preacher and Hayes, 2004). Thus, the result that burnout mediated the pathway between family incivility and job satisfaction is consistent with previous research findings (Paul et al. , 2021).…”
Section: Discussionsupporting
confidence: 92%
“…, 2021). Research has revealed adequate evidence (Paul et al. , 2021) confirming the association between family incivility and adverse work outcomes, namely job satisfaction.…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%
See 3 more Smart Citations